BORDER DESIGNING AND IT’S DECORATION IN MUGHAL MINIATURE PAINTINGS - Shanker, Hari Om (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Mughal emperors had a keen interest in painting, due to which, under their rule, painting again started progressing rapidly on the development side. The development of painting began with the rule of Babur, the founder of the Mughal Empire, and continued till the end of Shah Jahan’s reign. The development of painting started during the reign of Akbar and the painting reached its climax during the reign of Jahangir. Border designing or hashiya of Mughal paintings were also made by skilled artists, who were perfect in making only hashiya. Along with the picture, there was a practice of tying the picture to the khat all around. Pratap (2017). These khats were decorated with beautiful ornate designs. In addition to bell-boots, these borders had anthropomorphic or hunting related designs. Often the gold or silver plates were sprinkled on the hashiya or they were divided into small and large khat in flat two-three colors.